1993
DOI: 10.1021/la00026a020
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, structural characterization, and thermal behavior of layer-by-layer deposited ultrathin films of poly(vinyl sulfate) and poly(allylamine)

Abstract: We have recently introduced a new method of creating homogeneous ultrathin films on solid supports, which is based on the electrostatic attraction between opposite charges. Consecutively alternating adsorption of anionic and cationic polyelectrolytes from their aqueous solution leads to the formation of multilayer assemblies. The multilayer buildup is easily monitored by small angle X-ray scattering (SAXS) and a linear increase of the film thickness with the number of adsorbed layers is observed. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
643
6
15

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 908 publications
(681 citation statements)
references
References 0 publications
17
643
6
15
Order By: Relevance
“…In previous multilayer systems, based on isopolyanions, it is known that the presence of protons in the adsorption solution significantly enhances the quantity of the anion that is reversibly adsorbed [16]. In addition to this when 0.5M Na 2 SO 4 is used as the electrolyte instead of 0.5M NaHSO 4 there is a lower amount of the anion adsorbed, proving it is indeed the presence of protons and not the ionic strength that causes this strong absorption between the anion and the electrode. It was found that the peak currents associated with the tungsten-oxo framework were in the range of 1.4 x 10 -6 to 2.0 x 10 -6 A when the solution from which the anion is adsorbed is aqueous 0.5M NaHSO 4, and only 2.5 x 10 -7 to 7.0 x 10 -7 A with poorer ill defined redox processes, when the solution is the more alkaline aqueous 0.5M Na 2 SO 4. , the peak currents increase in a step-wise fashion corresponding to the addition of one monolayer, namely 1.39 x 10 -11 mol cm -2 , which is typical of monolayer coverages for multilayer systems [20].…”
Section: Electrochemical Characterisation Of Assembled Multilayers Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous multilayer systems, based on isopolyanions, it is known that the presence of protons in the adsorption solution significantly enhances the quantity of the anion that is reversibly adsorbed [16]. In addition to this when 0.5M Na 2 SO 4 is used as the electrolyte instead of 0.5M NaHSO 4 there is a lower amount of the anion adsorbed, proving it is indeed the presence of protons and not the ionic strength that causes this strong absorption between the anion and the electrode. It was found that the peak currents associated with the tungsten-oxo framework were in the range of 1.4 x 10 -6 to 2.0 x 10 -6 A when the solution from which the anion is adsorbed is aqueous 0.5M NaHSO 4, and only 2.5 x 10 -7 to 7.0 x 10 -7 A with poorer ill defined redox processes, when the solution is the more alkaline aqueous 0.5M Na 2 SO 4. , the peak currents increase in a step-wise fashion corresponding to the addition of one monolayer, namely 1.39 x 10 -11 mol cm -2 , which is typical of monolayer coverages for multilayer systems [20].…”
Section: Electrochemical Characterisation Of Assembled Multilayers Ofmentioning
confidence: 99%
“…The technique of consecutive adsorption of anionic and cationic layers has been well documented by, for example, Decher et al [2][3][4] who reported on various systems involving these electrostatic interactions. Films with alternating layers of the anion cobalt phthalocyanine tetrasulphonate and cationic polydimethyldiallylammonium chloride prepared by electrostatic layer-by-layer adsorption were reported by Lvov et al [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logo, Decher estendeu a técnica para camadas de polieletróli-tos 17 exclusivamente e filmes com várias camadas puderam ser obtidos da mesma maneira. Desde então, os mais diferentes materiais orgânicos vêm sendo depositados pelo método proposto por Decher.…”
Section: Filmes Automontados (Am)unclassified
“…5 eram bastante homogêneos e exibiam franjas de interferência periódicas, quando observados por espalhamento de raios X de baixo ângulo, revelando um ordenamento no filme em relação à sua direção normal, mais precisamente uma estrutura de camadas. Posteriormente, Decher e colaboradores estenderam o método para a deposição de polieletróli-tos 15,17 , inicialmente depositando camadas de poliânions alternadas com camadas de moléculas anfifílicas catiônicas, e camadas de policátions alternadas com camadas de moléculas anfifílicas aniônicas 15 . Novamente observaram que cada camada positiva após a deposição da camada de policátion, pode haver sítios com cargas negativas, sendo estes originários de segmentos de cadeias de poliânions que interpenetraram através do filme.…”
Section: Os Trabalhos De Decherunclassified